Sustaining the flame: STIB in nurturing permanence - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Waswa, Boaz Shaban (2024)
Socio-Technical Innovation Bundles (STIBs) are transforming the agri-food systems as farmers integrate diverse socio-technical innovation bundles. Practices have evolved as technologies take root.